REGISTRATION INFORMATION SYSTEM XYZ HOTEL ROOMS IN USING VISUAL BASIC 6.0 - Herdiman Setyawirawan; Ir. Aqwam Rosadi Kardian, MM (Jurnal Sistem Informasi, 2002)
In order to support the smooth process of registration of hotel rooms at XYZ, computerized system that will greatly assist the author intended. Computerized system is required for a better and optimal.The system is meant is the data flow system of symbols used in flow program itself, for example, the symbol of process, a symbol of manual work, document symbol, the symbol stream from the process, the symbol of a computer process, a symbol of foreign operations.This research also suggests writing about Registration Information System in Hotel Room XYZ included with problems arising during the execution of the work process itself.